Tuning Ground States of Bis(triarylamine) Dications: From a Closed‐Shell Singlet to a Diradicaloid with an Excited Triplet State1. (3rd February 2014) - Su, Yuanting; Wang, Xingyong; Zheng, Xin; Zhang, Zaichao; Song, You; Sui, Yunxia; Li, Yizhi; Wang, Xinping
Abstract Three bis(triarylamine) dications were isolated by using weakly coordinating anions. Their electronic structures in the ground state were investigated by various experiments in conjunction with theoretical calculations. The ground‐state electronic structures of these species were tunable by substituent effects, with two of them as closed‐shell singlets and one of them as an open‐shell singlet in the solid state. The excited state of the latter is thermally accessible, indicated by EPR and SQUID measurements. The work provides a new and stable diradicaloid structure motif with an excited triplet sate.